Evaluation on Effectiveness of CVD and PVD Coated Tools during Dry Machining of Incoloy 825. Issue 6 (1st November 2016) - Thakur, A.; Gangopadhyay, S.; Maity, K. P.; Sahoo, S. K.
ABSTRACT: With wide applications of nickel-based superalloys in strategic fields, it has become increasingly necessary to evaluate the performance of different advanced cutting tools for machining such alloys. With a view to recommend a suitable cutting tool, the present work investigated various machinability characteristics of Incoloy 825 using an uncoated tool, chemical vapor deposition (CVD) of a bilayer of TiCN/Al2 O3, and physical vapor deposition (PVD) of alternate layers of TiAlN/TiN-coated tools under varying machining conditions. The influence of cutting speed (51, 84, and 124 m/min) as well as feed (0.08, 0.14, and 0.2 mm/rev) was comparatively evaluated on surface roughness, cutting temperature, cutting force, coefficient of friction, chip thickness, and tool wear using different cutting tools. Although the CVD-coated tool was not useful in decreasing surface roughness and temperature, a significant reduction in cutting force and tool wear could be achieved with the same coated tool under a high cutting speed of 124 m/min. On the other hand, the PVD-coated tool outperformed the other tools in terms of machinability characteristics. This might be attributed to the excellent antifriction and antisticking property of TiN and good toughness due to the multilayer configuration in combination with a thermally resistant TiAlN phase. Adhesion, abrasion, edge chipping, and nose wear were the prominent wear mechanisms of the uncoated tool, followed by the CVD-coated tool. However, remarkable resistance to such wear was evident with the PVD TiAlN/TiN multilayer-coated tool.